Indonesian Legal Dynamics In Global Capitalism Reality: Analysis of the Formation of Indonesia’s Regulations - Imam Mahdi (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2022)
The formation of regulations cannot be separated from the dimension of the legal report. The formation of law in Indonesia is a compromise of political elites in Indonesia's multi-party government system. Not only is the formation of laws purely a legal product, but also as a political product. In fact, it is a struggle between political interests that underlie and collaborate among the interests of various parties, including foreign interests. Therefore, in the practice of forming laws in Indonesia, there are often deviations from the ideological foundation of the state starting from the old order era, the new order and the current era of reform. This research reveals the main causes of these irregularities